A qualitative case study of a Korean former addict's existential self‐interpretation and identity transformation. Issue 2 (24th February 2020) - Kang, Sun Kyung; Shin, Seungnam; Sang, Chong Ryel
Abstract: This study explored the case of a former addict, focusing on his existential self‐interpretation and identity transformation process. This study began from the question of whether philosophical processes related to existential self‐interpretation could lead to the formation of the concept of bottoming out and of identity transformation. To answer this question, the study analyzed the case of a male in his mid‐forties who was addicted to drugs for approximately 30 years and has only recently maintained abstinence. The study used the phenomenological approach to determine the meaning drugs held for him in each stage, and what drug‐related identity he had in each stage. Further, this study identified the integrative implications of these meanings in terms of existential self‐interpretation and identity transformation. The four different identities the man identified for the four stages of his life were juvenile delinquent, gang member, half‐gangster, and breadwinner, and the associated meanings drugs had for him during each period were "glue, " "filthy, " "leeches, " and "abstinence, " respectively. Finally, this study elucidated the integration of these meanings through the hermeneutic circle, identified the social welfare implications of the findings, and developed educational recommendations.